Acceptance and Utilisation of Sulphadoxine-Pyrimethamine and Insecticide-Treated Nets among Pregnant Women in Oyo State, Nigeria. (29th December 2015) - Adeola, Aderonke A.; Okwilagwe, Eugenia A.
Abstract : The study is an investigation of the acceptance and utilisation of Sulphadoxine-Pyrimethamine (Fansidar), the drug of choice for Intermittent Preventive Treatment in pregnancy, and Insecticide-Treated Nets among pregnant women who access different health facilities in Oyo State, Nigeria. Pregnant women (582) attending government primary healthcare antenatal clinics and 50 attending faith clinics purposively selected responded to structured instruments that were analysed using percentages, t -test correlation, and multiple regression. Acceptance and utilisation of RBM tools were higher in government clinics than faith clinics and in rural areas. Pregnant women in government clinics, 60.8% and 66.8%, and faith clinics, 18% and 38.0%, utilised Roll Back Malaria tools, significant att ( 630 ) = 5.81, p ≤ 0.05, andt ( 630 ) = 3.99, p ≤ 0.05, respectively. Pregnant women in rural locations who accessed government clinics utilised Roll Back Malaria tools more than those in urban areas, t ( 580 ) = - 641, p ≤ 0.05 . Number of pregnancies, educational qualification of the pregnant women, and marital status significantly and consistently influenced acceptance and utilisation of these tools. To ensure that set targets are met, the utilization of RBM tools among the two categories of pregnant women can be improved by increasing the supply of the tools and ensuring that treatment is free.